PENGEMBANGAN APLIKASI BERBASIS ANDROID BeMAU UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK USIA DINI - Noor Rokhmah Affifah; Umi Faizah (QURROTI, 2023)
The background of this research is the lack of learning media to improve AUD reading skills in the digital era. The formulation of the research problems are: 1) what is the design for the development of the "BeMAU" android application to improve AUD reading skills?; 2) how is the implementation of the android application "BeMAU" to improve AUD reading skills?; 3) what is the feasibility of the "BeMAU" android application to improve AUD reading skills? While the objectives are 1) to find out the design of the "BeMAU" android application development to improve the ability to read AUD; 2) to find out the application of the android application media "BeMAU" to improve the ability to read AUD; 3) to determine the feasibility of the "BeMAU" android-based application to improve AUD reading skills. This study uses the R&D method and produces the android application "BeMAU" to improve reading skills in AUD. The data collection technique used is the method of observation, questionnaires, documentation. The research subjects were RA Al Fitroh Tempel's children aged 5-6 years. The results of the study are: 1) Development design must be considered in the development of the "BeMAU" android application, namely: (1) display animation design, (2) font selection, (3) coloring, (4) word selection (5) clarity in each reading . 2) the procedure for implementing the "BeMAU" android application is as follows: (1) conditioning children with classical, (2) introducing letters by singing and playing guessing, (3) introducing the "BeMAU" android application, (4) inviting children to learn by â€œBeMAUâ€ application. 3) the feasibility and potential of developing the android application "BeMAU" to improve AUD reading skills is proven to be suitable for use in PAUD as evidenced by a media expert validation score of 4.4; material experts 4.3; practitioner 4,6; 4.7 grade teachers and children's questionnaires.